Humoral response rate and predictors of response to BNT162b2 mRNA COVID19 vaccine in patients with multiple myeloma. (1st July 2021) - Avivi, Irit; Balaban, Roi; Shragai, Tamir; Sheffer, Gabi; Morales, Miguel; Aharon, Anat; Lowenton‐Spier, Noa; Trestman, Svetlana; Perry, Chava; Benyamini, Noam; Mittelman, Moshe; Tabib, Yaara; et al.
Summary: Multiple myeloma (MM) patients are at excess risk for clinically significant COVID19 infection. BNT162b2 mRNA COVID19 (BNT162b2) vaccine provides effective protection against COVID19 for the general population, yet its effect in MM patients may be compromised due to disease and therapy‐related factors and was not yet evaluated. This single‐centre prospective study included MM patients tested for serological response 14–21 days post second vaccine. Vaccinated healthy volunteers served as controls. In all, 171 MM patients, median age 70 (38–94) were included; 159 active MM and 12 smouldering myeloma (SMM). Seropositive response rate (median titer) was 76% (91 U/ml) in active MM patients vs 98% (992 U/ml) in the 64 controls ( P < 0·0001), and 100% (822 U/ml) in SMM patients. Multivariate analysis revealed older age ( P = 0·009), exposure to ≥4 novel anti‐myeloma drugs ( P = 0·02) and hypogammaglobulinaemia ( P = 0·002) were associated with lower response rates. None of the novel agents significantly decreased response rate, whereas daratumumab trended towards reduced response ( P = 0·08). Adverse events occurred in 53% and 55% of the MM patients and controls, respectively, all transient grade 1–2. In conclusion, BNT162b2 vaccine was safe and provided a high seropositivity rate in MM patients, independent of treatment type. Older, hypogammaglobulinaemic and heavily pretreated patients had lower response rates.